Eosinophilic myocarditis presenting as acute coronary syndrome - Evrim Şimşek; Filiz Özerkan Çakan; Mustafa Akın (KARE Publishing, 2017)
Eosinophilic myocarditis (EM) is a rare condition that may result from several heterogeneous eosinophilic diseases, including parasite infection, hypersensitivity reaction, vasculitis, and hypereosinophilic syndrome. Regardless of etiology, the disease may present with various cardiac conditions, such as acute coronary syndrome, heart failure, or arrhythmia. Irreversible endomyocardial fibrosis, which causes restrictive cardiomyopathy, occurs in the late phase of the disease. Early diagnosis and treatment is crucial to prevent disease progression. Presently described is a case of EM presenting as acute coronary syndrome that was treated with steroids.